“Parting is such sweet sorrow [...]”, or the perils of publishing papers in parts: the case of the nomenclatural novelties published by Raymond Hamet (1890–1972) in his two-part monograph (1907, 1908) of Kalanchoe (Crassulaceae subfam. Kalanchooideae), with special reference to the new names and new combinations treated (but not first published) in part 2 - Smith, Gideon F.; Monro, Anna M. (Phytotaxa, 2024)
When still a teenager, Raymond Hamet (1890–1972) published a two-part, 64-page monograph of Kalanchoe (Crassulaceae subfam. Kalanchooideae) in which 51 accepted species, one accepted nothospecies, and ten species of unresolved application (“Species non satis notæ”) were included. The first part of the monograph appeared in November 1907 and the second (and final) part was published in January 1908. In addition to treating the three new names that were unambiguously validly published in part 1, Hamet (in 1907) also mentioned and provided sufficient descriptive text to validly publish one new name and one of the two new combinations that were only formally treated in part 2 (in 1908). This matter is addressed to determine the correct dates and bibliographic citations for the nomenclatural novelties included in his monograph of Kalanchoe. It is shown that, with one exception, K. crenata (Baker 1883: 139) Hamet (1908: 19), nom. illeg. [here deliberately cited with its author attribution], all the names of new taxa and one new combination were validly published in part 1 (November 1907) of the monograph, despite some only being formally treated taxonomically in January 1908. In addition, despite disparate references to K. tieghemii in the second part of the monograph, i.e., the part published in January 1908, this name was also validly published in 1907 and not much later in 1914, as has been supposed.